Konsep Kehadiran Allah Berdasarkan Kitab Kejadian dan Implikasinya bagi Gereja Saat Ini - Matius Kalatiku (Sekolah Tinggi Teologi Kerusso Indonesia, 2021)
The concept of the presence of God in the midst of believers is very important, because when God is present all changes, the Book of Genesis records that before the world was created and the Spirit of God hovered in chaotic and formless world conditions. God's presence in Indonesia and especially for believers will have an impact and influence towards the better. Every believer must be a change agent and God's representative on earth, so that others can see and feel God's presence in real life. The church as an organization must also appear with all its existence for the life of the state and nation, the church must have